2021
DOI: 10.1177/09544070211065607
|View full text |Cite
|
Sign up to set email alerts
|

Study on the leakage of plunger pair under static condition in high-pressure common rail injector considering deformation effect

Abstract: Plunger pair is the key component of high pressure common rail injector and its sealing performance is very important. Therefore, it is of great significance to study the leakage mechanism of plunger pair. Under static condition, the high-pressure fuel flow in the gap of the plunger pair caused the deformation of the plunger pair structure and the temperature rise of fuel. For a more comprehensive and accurate study, the effect of deformation, including elastic deformation and thermal expansion, the physical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This research demonstrates that the thermal deformation of plunger-sleeve can be effectively reduced by selecting sleeves with large thermal expansion coefficient and plungers with small thermal expansion coefficient, which can improve the sealing of the plunger-sleeve. Gao et al 13 analyzed the effects of the fuel leakage rate response by elastic deformation. It was demonstrated that when the elastic deformation of the plunger-sleeve is not considered, the fuel leakage rate of the plunger-sleeve increases linearly with an increase in the inlet pressure, whereas when the elastic deformation is considered, the leakage rate and inlet pressure exhibit a nonlinear relationship.…”
Section: Introductionmentioning
confidence: 99%
“…This research demonstrates that the thermal deformation of plunger-sleeve can be effectively reduced by selecting sleeves with large thermal expansion coefficient and plungers with small thermal expansion coefficient, which can improve the sealing of the plunger-sleeve. Gao et al 13 analyzed the effects of the fuel leakage rate response by elastic deformation. It was demonstrated that when the elastic deformation of the plunger-sleeve is not considered, the fuel leakage rate of the plunger-sleeve increases linearly with an increase in the inlet pressure, whereas when the elastic deformation is considered, the leakage rate and inlet pressure exhibit a nonlinear relationship.…”
Section: Introductionmentioning
confidence: 99%